Penyisihan Logam Fe Pada Air Gambut Menggunakan Membran Chitosan Sebagai Adsorben: Removal of Fe From Peat Water Using Chitosan Membrane As Adsorbent - Khadijah Lestari Lubis; Shinta Elystia; Dini Aulia Sari Ermal; Zultiniar Zultiniar (LPPM Universitas Mataram, 2022)
Peat water in terms of quality cannot be used as a source of clean water or drinking water, so it needs to be processed. One alternative treatment that can be used is the adsorption process with a column system using a chitosan membrane (the content of amine groups contained in the chitosan membrane has a good ability to absorb metals). This study aims to remove Fe metal in peat water. Variations carried out were Fe concentrations of 2, 3 and 4 mg/L and flow rates of 2, 3, 4 and 5 mL/minute. The results obtained are the best Fe metal removal efficiency of 92.20% with a final concentration of 0.312 mg/L at an Fe concentration of 4 mg/L and a flow rate of 2 mL/minute. The results of the study have met the quality standards set by the Minister of Health of the Republic of Indonesia Number 32 of 2017 concerning Sanitary Hygiene